PARENTAL INVOLVEMENT TO OVERCOME SECONDARY STUDENTS’ FOREIGN LANGUAGE ANXIETY - Nukmatus Syahria (Fakultas Ilmu Budaya, Universitas Brawijaya, 2022)
Among the many problems the students faced in learning English, especially in Speaking skill, many of the recent studies mentioned anxiety as one of the common psychological issue. One of the solutions emerged is by being aware and by improving parental involvement in language learning. The aims of this study are to investigate the students’ anxiety during Speaking as well as to describe the parental involvement to overcome students’ Foreign Language Anxiety (FLA). This descriptive qualitative study applied descriptive analysis which focused on the lived experience of secondary students and their parents role to help them to cope up with their Speaking anxiety. Semi-structured interview and classroom observation were used to collect the data. There were 5 students and 5 parents participated. The result showed that the students were anxious the most about Speaking test and during presentation. Another finding also showed that parents involved themselves the most by fulfilling students’ academic needs and give their children encouragement in learning English. This study have implications for parents, students and teachers in the attempt to overcome FLA among EFL students.